Control of Milk Fermentation in Batch Bioreactor - Ritonja, Jozef; Gorsek, Andreja; Pecar, Darja (Elektronika ir Elektrotechnika, 2020)
In this paper, modelling and control of a batch bioreactor is studied. A main disadvantage of batch bioreactors compared to other types of bioreactors is their inability to introduce biological or/and chemical substances during operation. Therefore, possibility of bioreactor’s control by means of changing temperature was proposed, analyzed, and implemented. A new supplementary input/output dynamical mathematical model, which considers influence of heating and cooling on a bioprocess, was developed. On a basis of this model, a control system was designed and a method for tuning of the controller was suggested. Results show characteristics, applicability, and advantages of the presented approach.